Cement concrete pavement joint and crack pouring construction method
Through the combination of aggregate, adhesive and waterproof materials, a semi-rigid seam filling structure is constructed, which solves the problems of numerous processes and insufficient durability in cement concrete pavement joints and crack seam filling methods, and improves the road driving comfort and use Lifespan and reduce costs.
Patent Information
- Application Number
- CN202310690534.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing cement concrete pavement joints and cracks filling methods have problems such as a variety of processes, insufficient durability and poor construction quality. The existing materials cannot simultaneously have sufficient strength, elastic recovery rate, adhesion, weather resistance and embedding resistance. Features lead to insufficient driving safety and service life.
The combination of aggregate, adhesive and waterproof material is used to form a porous skeleton structure and waterproof layer. Through the steps of clearing the seam, filling the aggregate, pouring the adhesive and pouring the waterproof material, a semi-rigid seam filling structure is constructed. Improve the waterproof effect and bearing capacity of the seams.
It has achieved the improvement of the driving comfort and service life of cement concrete pavement, reduced costs, enhanced the bearing capacity and waterproof performance of the joints, and effectively improved the aesthetics and protective effect of the pavement.
Smart Images

Figure CN119121735A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to cement concrete pavement construction and repair, and in particular to a cement concrete pavement joint and crack filling construction method. Background Art
[0002] Cement concrete pavement usually needs to have multiple joints to avoid thermal expansion and contraction, such as contraction joints and expansion joints. However, the existence of joints can easily lead to poor waterproofing, pavement base material overflow, edge damage, pavement hollowing, mud pumping, panel damage and fracture, etc., which not only affects driving safety and comfort, affects the appearance of the road, but also reduces the service life of the road. Therefore, it is necessary to treat the joints of cement concrete pavement.
[0003] There are two types of existing joint fillers: normal temperature construction type and heated construction type. Normal temperature construction type joint fillers mainly include polyurethane, silicone resin, chloroprene rubber mud, asphalt rubber, etc.; heated construction type joint fillers mainly include asphalt mastic, polyvinyl chloride mastic, modified asphalt, etc. Affected by the requirements of road use and climate, joint fillers need to have sufficient strength and elastic recovery rate, sufficient adhesion and flexibility, and also have weather resistance, fatigue resistance, embedding resistance, water insolubility, and water impermeability. However, existing materials cannot have the above characteristics at the same time. Even if some materials have excellent performance and multiple characteristics, the cost is high and the engineering practice value is lost. Therefore, the project needs to select the appropriate materials according to the use requirements and economy, but some functions are weakened or even lost.
[0004] Foam strip + 1-1.5cm suspended sealant is one of the commonly used joint filling forms. The foam strip is embedded in the bottom of the joint, the sealant seals the top of the panel, and the middle of the joint is a cavity. Engineering practice shows that relying solely on suspended sealant for filling is prone to cracking and fatigue, and it is difficult to truly meet the requirements of road use. Therefore, it is necessary to improve the existing materials and processes.
[0005] In the context of my country's vigorous and continuous development of transportation infrastructure in the past two or three decades, the road mileage has increased dramatically. Now, old roads account for the vast majority of roads. The trend of road repair and upgrading is inevitable, and the proportion of road repair is increasing. Traditional joint re-filling has many processes, including cutting, cleaning, embedding, and filling, and the unit price is low, so the construction quality is uneven. Therefore, the joint re-filling method also needs to be improved.
[0006] In addition, there are two main methods for repairing cracks in existing cement concrete pavements. One is to expand the cracks into 20mm×20mm (width×depth) grouting grooves by cutting, and then pouring sealing materials into the grooves to seal and waterproof; the other is to pour asphalt materials directly on top of the pavement cracks for sealing and waterproofing. In the above two methods, the materials used for crack repair are mainly asphalt-based materials, which have the advantages of being fast and able to be opened to traffic immediately after the repair is completed, but asphalt-based materials have poor resistance to temperature changes and weathering and a short service life. In addition, the use of grooving for repairs will also aggravate the damage to the road surface, and at the same time increase hidden dangers such as gnawing, which is not conducive to road driving. Summary of the invention
[0007] In order to overcome the problems of numerous processes, insufficient durability, poor construction quality, etc. in the above-mentioned prior art, the present invention provides a construction method for grouting joints and cracks in cement concrete pavement, in which aggregates, adhesives and waterproof materials are filled in the joints or cracks to form a grouting structure with good strength, bonding performance, impermeability, fatigue resistance and other characteristics, so as to improve the driving comfort and service life of the cement concrete pavement, which not only saves resources and reduces costs, but also produces good economic and social benefits.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A cement concrete pavement joint grouting construction method comprises the following steps:
[0010] S1. Seam cleaning: Use a seam cleaning machine to cut a new seam with a width of 4 to 6 mm and a depth of 1 / 3 to 2 / 5 of the thickness of the road panel at the joint of the road panel. The seam width is preferably 5 mm. Alternatively, use a seam cleaning machine to cut the old filler along the old seam, then clean the seam, grind the inner wall of the seam to make it smooth, and remove the old filler and debris in the seam;
[0011] S2. Filling in aggregate: After cleaning the joints, fill the joints with clean and dry aggregates, and level the surface of the aggregates until it is flush with the road slab;
[0012] S3. Pouring adhesive: Evenly pour the adhesive into the aggregate at the joints, and then cure until the adhesive solidifies to form a porous skeleton structure;
[0013] S4. Pouring waterproof material: After the adhesive solidifies, evenly pour the waterproof material on the joint surface. The waterproof material penetrates into the joint and forms a waterproof layer on the joint surface. The waterproof layer is maintained until the surface is non-sticky, thus forming a grouted structure.
[0014] It should be noted that in S2, the aggregate includes quartz particles or slag particles, and the particle size is 1 / 5 to 1 / 2 of the joint width. The quartz particles include river sand and quartz sand, and the slag particles include brown corundum and black gold sand.
[0015] It should be noted that in S3, the adhesive includes components A1 and B1, and the mass ratio of the two components is 2:1 to 5:1, preferably 3:1. Component A1 includes 40% to 55% by mass of E51 epoxy resin, 5%-10% by mass of flexibility modifier, and 30% to 40% by mass of diluent, and component B1 includes 50% by mass of epoxy curing agent and 50% by mass of diluent; the flexibility modifier includes styrene-butadiene rubber and polypropylene glycol ether; the diluent includes β-hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, xylene, and benzyl alcohol; the epoxy curing agent adopts an amine curing agent, including bisphenol A epoxy resin, which can cross-link and cure the epoxy resin at room temperature.
[0016] It should be noted that, in S3, the pouring mass ratio of the adhesive to the aggregate is 1:10 to 1:15.
[0017] It should be noted that in S3, the physical and mechanical properties of the adhesive are as follows: construction viscosity ≤600mPa·s, tensile strength after curing ≥20MPa, compressive strength after curing ≥35MPa, flexural strength after curing ≥20MPa, 7d tensile bonding strength ≥2.5MPa or substrate damage, solid content ≥50%, surface drying time at room temperature ≤12h, and actual drying time at room temperature ≤24h.
[0018] It should be noted that in S3, the porosity of the porous skeleton structure is 30% to 40%.
[0019] It should be noted that in S4, the waterproof material includes components A2 and B2, and the mass ratio of the two components is 3:7. The A2 component includes 80% to 85% by mass of polyether polyol, 2% to 3% by mass of low molecular weight cross-linking agent, 1% to 2% by mass of water, 10% to 15% by mass of additives, 0.3% to 0.5% by mass of defoaming agent and 0.03% to 0.07% by mass of catalyst; the B2 component is a polyurethane prepolymer, wherein the NCO value is 3% to 5% (the NCO value refers to the mass of isocyanate (-NCO) groups contained in 100g of sample), and the solid content is ≥80%; the additives include color paste and filler, the color paste is used to adjust the color of the material, and the filler can improve the strength of the material while reducing the cost of the material; the catalyst is used to adjust the reaction speed of each component material in the waterproof material, and the defoaming agent is beneficial to eliminate the bubbles generated in the waterproof material.
[0020] It should be noted that the low molecular weight cross-linking agent includes propylene glycol and ethylene glycol, preferably propylene glycol; the polyether polyol adopts a bifunctional polymer polyether with an average molecular weight greater than or equal to 2000; the defoaming agent adopts an organosilicon defoaming agent, including polydimethylsiloxane and ethylene glycol siloxane, preferably polydimethylsiloxane; the catalyst includes dibutyltin dilaurate; the color paste includes an oily color paste, and the colors are mainly black and white; the filler includes talcum powder, barium sulfate powder, and calcium carbonate powder.
[0021] It should be noted that in S4, the physical and mechanical properties of the waterproof material are as follows: leveling (L type) is smooth and flat, surface drying time ≤16h, elastic recovery rate ≥80%, tensile modulus at 23°C ≤0.4MPa, tensile modulus at -20°C ≤0.6MPa, and the adhesion to concrete is not destroyed by immersion in water, oil, and artificial aging.
[0022] It should be noted that in S4, the thickness of the waterproof layer on the joint surface is 1 to 2 mm.
[0023] It should be noted that, in S4, the horizontal plastic deformation range of the grouting structure is 10% to 15%, and the compressive strength is ≥5MPa.
[0024] According to another aspect of the present invention, a method for grouting cracks in a cement concrete pavement is provided, and the method is different from a method for grouting joints in a cement concrete pavement in that: in S1, when grouting pavement cracks with a width ≥ 2 mm, there is no need to use a crack cleaning machine to cut the cracks, and the crack cleaning process is directly performed to grind the inner wall of the crack and remove debris from the crack.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The present invention innovatively proposes a cement concrete pavement joint grouting construction method, which adopts a combination of aggregate, adhesive and waterproof material, and implants a semi-rigid grouting structure in the joint. Aggregate is the skeleton of the grouting structure and serves as the main load-bearing part; the adhesive not only effectively bonds the aggregate, but also effectively bonds the grouting structure with the two side walls of the joint, and plays the role of force transmission and dispersion. Its bonding and filling effect with the aggregate enables it to also carry the waterproof material; the waterproof material not only further fills the gaps in the grouting structure and Further bonding can be carried out and the gaps on the surface of the caulking structure can be sealed, forming a thin waterproof layer on the surface of the caulking structure, thereby achieving the purpose of three-dimensional waterproofing. With the cooperation of adhesives and aggregates, the waterproof effect of the joints can be further improved. That is, the new caulking structure has multiple technical effects such as load-bearing, bonding, compressible deformation (plasticity), waterproofing, fatigue resistance, and anti-embedding, thereby improving the bearing capacity of the joints, driving comfort, and the appearance of the road surface, effectively improving road surface diseases such as flooding of base materials and edge damage, and extending the service life of cement concrete pavement.
[0027] 2) The waterproof material used in the present invention has the characteristics of low cohesive energy, good flexibility, fatigue resistance, no inorganic filler, high ductility, etc. It can penetrate well into the gaps between solid particles and adhesives in a flowing state, and can form a dense waterproof and anti-seepage bonding layer on the upper part of the new caulking structure in a solid state. Additives can be added to the waterproof material as needed to make the surface of the new caulking structure smooth and beautiful, and it also has the characteristics of no cracking, no falling off, puncture resistance, tearing resistance, flexibility and durability, weather resistance, and aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a flow chart of the construction method for filling joints and cracks in cement concrete pavement.
[0029] Figure 2 Schematic diagram of joints or cracks and caulking structure of cement concrete pavement; wherein, Figure (a) is a schematic diagram of joints or cracks, and Figure (b) is a schematic diagram of caulking structure, road panel 101, joints or cracks 102, caulking structure 103, aggregate 301, adhesive 302, waterproof material 303.
[0030] Figure 3 Schematic diagram of the old joint of the pavement in Example 1, wherein Figure (a) is a schematic diagram of the old joint and the old filler, and Figure (b) is a schematic diagram of the old joint after the cleaning treatment.
[0031] Figure 4 Schematic diagram of filling old joints in pavement of Example 2, wherein Figure (a) is a schematic diagram of filling the joints with aggregate, and Figure (b) is a schematic diagram of pouring waterproof material into the joints.
[0032] Figure 5Schematic diagram of pavement crack filling in Example 3, wherein Figure (a) is a schematic diagram of filling the cracks with aggregate, and Figure (b) is a schematic diagram of pouring consolidation glue into the cracks. DETAILED DESCRIPTION
[0033] The present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments. Obviously, the following embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.
[0034] Embodiment 1;
[0035] See also Figures 1 to 3 This embodiment relies on a road repair project of a certain section of Qinglian Expressway (G0421). The expressway is 216km long, with four lanes in both directions and a design speed of 80-100km / h. It was fully opened on January 25, 2011 and has been in operation for about 12 years. The original caulking material is a single-component polyurethane sealing material. Due to the long operation time, the plasticity of the foundation is gradually enhanced, and the stress state of the sealing material in the joint has undergone a very obvious change, from the horizontal force to the vertical shear force. The caulking material needs to withstand hundreds of thousands of unstable forces within 24 hours. Therefore, the traditional joint caulking method can no longer meet the requirements of the current situation. If the joint sealing material is replaced according to the traditional method, the replaced sealing material will soon age and the two walls will fall off due to the above reasons, making it difficult to play a role in sealing and waterproofing.
[0036] The caulking object of this embodiment is an old road surface joint, and the construction is carried out using a cement concrete road surface joint caulking construction method described in the present invention, and the method comprises the following steps:
[0037] S1. Seam cleaning:
[0038] Since the old joints of the road surface are to be refilled, a joint cleaning machine is used to cut the old filler along the old joints. The cutting width is about 10mm and the cutting depth is about 15-20mm. Then the joints are cleaned, the inner wall of the joints is polished, and the old filler and debris in the joints are removed;
[0039] The gasoline engine power of the seam cleaning machine used is 9-13HP, the saw blade diameter is 400-500mm, and the saw blade linear speed is 47-59m / s; grinding is completed by an electric grinder, and debris is removed by blowing with an air pump or flushing with a high-pressure water pump;
[0040] S2. Fill in aggregate:
[0041] After cleaning the joints, fill the joints with clean, dry corundum with a particle size of 3 to 5 mm as aggregate, and level the surface of the aggregate until it is flush with the road slab;
[0042] S3, pouring adhesive:
[0043] The adhesive was evenly poured into the aggregate at the joints, with the pouring mass ratio of adhesive to aggregate being 1:12.5, and then cured until the adhesive solidified to form a porous skeleton structure. The measured porosity of the porous skeleton structure was 34.8%.
[0044] The adhesive comprises components A1 and B1, and the mass ratio of the two components is 3:1. Component A1 comprises 55% by mass of E51 epoxy resin, 10% by mass of flexibility modifier, and 35% by mass of diluent, and component B1 comprises 50% by mass of epoxy curing agent and 50% by mass of diluent; the flexibility modifier adopts polypropylene glycol ether, and the diluent comprises β-hydroxyethyl methacrylate; the epoxy curing agent adopts bisphenol A epoxy resin, which can cross-link and cure the epoxy resin at room temperature;
[0045] The measured physical and mechanical parameters of the adhesive are as follows: construction viscosity 510mPa·s, tensile strength after curing 32.6MPa, compressive strength after curing 54MPa, flexural strength after curing 24MPa, 7d tensile bond strength 2.55MPa, solid content 65%, surface drying time at room temperature 6h, actual drying time at room temperature 18h;
[0046] S4, pouring waterproof material:
[0047] After the adhesive solidifies, the waterproof material is evenly poured on the joint surface. The waterproof material penetrates into the porous skeleton structure and forms a waterproof layer with a thickness of 1.4 mm on the joint surface. The waterproof layer is cured for 1 to 2 hours until the surface of the waterproof layer is non-sticky, thus forming a caulking structure.
[0048] The waterproof material comprises components A2 and B2, and the mass ratio of the two components is 3:7. The A2 component comprises 84.7% by mass of a bifunctional polymer polyether (average molecular weight above 2000), 2% by mass of a low molecular cross-linking agent, 1.5% by mass of water, 11.5% by mass of an additive, 0.3% by mass of a defoaming agent, and 0.05% by mass of a catalyst; the B2 component is a polyurethane prepolymer, wherein the NCO value is 3.52% and the solid content is 80.3%; the low molecular cross-linking agent is propylene glycol; the additive is an oily color paste, which is a mixture of black and white pastes in a certain proportion, and the color paste is used to adjust the color of the waterproof material, which is beneficial to the appearance; the catalyst is dibutyltin dilaurate, which is used to adjust the reaction speed of each component material in the waterproof material; the defoaming agent is polydimethylsiloxane, and the defoaming agent is beneficial to eliminate bubbles generated in the waterproof material;
[0049] The physical and mechanical properties of the waterproof material are as follows: leveling (L type) is smooth and flat, the surface drying time is 2h, the elastic recovery rate is 95%, the tensile modulus at 23°C is 0.34MPa, the tensile modulus at -20°C is 0.46MPa, and the adhesion to concrete is not damaged by immersion in water, immersion in oil, and artificial aging;
[0050] The measured horizontal plastic deformation range of the caulking structure is 13.6%, and the compressive strength is 7.5MPa. It has good waterproof effect, good fatigue resistance and anti-embedding performance, and meets the use requirements.
[0051] Embodiment 2;
[0052] See also Figure 1 , 2 4. This embodiment relies on a road repair project of S312 Highway in Qinzhou, Guangxi. The grouting target is the cracks in the road surface. Affected by the undercutting, the maximum joint width is about 30 mm. The cement concrete road surface joint grouting construction method described in the present invention is used for construction. When grouting, the undercutting part is also filled with aggregate, poured with adhesive, and sprinkled with waterproof material. The grouting effect is good. In this way, the method described in this embodiment can not only re-grout the old joints of the road surface, but also grout the undercuts caused by the old joints, so that the road surface is restored to be flat, which is beneficial to road driving.
[0053] Embodiment 3;
[0054] See also Figure 1 , 2 5. The engineering of this embodiment is the same as that of embodiment 1, but the grouting target is the cracks in the road surface, and the crack width varies from 2 to 25 mm. The traditional crack repair method is to expand the crack first and then fill it with waterproof sealant, but the expansion of the crack will deepen the damage to the road surface, the working hours are long, and the quality and effect of the grouting are poor;
[0055] In this embodiment, a method for grouting joints in a cement concrete pavement according to the present invention is used to construct a crack with a width of about 3 to 12 mm in the project. The method comprises the following steps:
[0056] S1. Seam cleaning:
[0057] Since the cracks on the road surface are filled, and the crack width is ≥2mm, there is no need to use a crack cleaning machine to cut the joints. The joints can be cleaned directly, and the inner wall of the joints can be polished and the debris in the joints can be removed. The polishing is done with an electric grinder, and the debris is removed by blowing with an air pump or flushing with a high-pressure water pump.
[0058] S2. Fill in aggregate:
[0059] After cleaning the cracks, fill the cracks with clean, dry fine sand with a particle size of 2 to 5 mm as aggregate, and level the surface of the aggregate until it is flush with the road slab;
[0060] S3. Pouring adhesive:
[0061] The adhesive was evenly poured into the aggregate at the cracks, with the mass ratio of adhesive to aggregate being 1:15. The adhesive was then cured until the adhesive solidified to form a porous skeleton structure. The measured porosity of the porous skeleton structure was 36.4%.
[0062] The adhesive comprises components A1 and B1, and the mass ratio of the two components is 3:1. Component A1 comprises 60% by mass of E51 epoxy resin, 5% by mass of flexibility modifier, and 35% by mass of diluent, and component B1 comprises 50% by mass of epoxy curing agent and 50% by mass of diluent; the flexibility modifier is polypropylene glycol ether; the diluent is 1,6-hexanediol diacrylate; the epoxy curing agent is bisphenol A epoxy resin;
[0063] The adhesive has the following physical and mechanical properties: construction viscosity is 540mPa·s, tensile strength after curing is 34.5MPa, compressive strength after curing is 56.1MPa, flexural strength after curing is 21.8MPa, 7d tensile bonding strength is 2.56MPa, solid content is 61.4%, surface drying time at room temperature is 1.5h, and actual drying time at room temperature is 4h;
[0064] S4, pouring waterproof material:
[0065] After the adhesive solidifies, the waterproof material is evenly poured on the crack surface. The waterproof material penetrates into the porous skeleton structure and forms a waterproof layer with a thickness of 1.2 mm on the crack surface. The waterproof layer is cured for 1 to 2 hours until the surface of the waterproof layer is non-sticky, thus forming a grouting structure.
[0066] The waterproof material comprises components A2 and B2, the mass ratio of the two components is 3:7, the A2 component comprises 84.7% by mass of bifunctional polymer polyether (average molecular weight above 2000), 2% by mass of low molecular crosslinking agent, 1.5% by mass of water, 12.5% by mass of additives, 0.3% by mass of defoaming agent and 0.07% by mass of catalyst; the low molecular crosslinking agent is propylene glycol; the additives include color paste and filler, the filler is talcum powder, accounting for about 11% of the A2 component, the color paste is a mixture of black and white paste, accounting for about 1.5% of the A2 component; the B2 component is a polyurethane prepolymer, wherein the NCO value is 3.47% and the solid content is 85%; the defoaming agent is polydimethylsiloxane; the catalyst is dibutyltin dilaurate;
[0067] The physical and mechanical properties of the waterproof material are as follows: leveling (L type) is smooth and flat, the surface drying time is 2h, the elastic recovery rate is 93%, the tensile modulus at 23°C is 0.33MPa, the tensile modulus at -20°C is 0.41MPa, and the adhesion to concrete is not damaged by immersion in water, immersion in oil, and artificial aging;
[0068] The measured horizontal plastic deformation range of the caulking structure is 12.8%, and the compressive strength is 6.3MPa. It has good waterproof effect, good fatigue resistance and anti-embedding performance, and meets the use requirements.
[0069] The following advantages are achieved when the method described in this embodiment is used to fill cracks in a road surface: there is no need to expand the cracks, which will not deepen the damage to the road surface, and it can also play a role in reinforcing the road surface; it can repair small cracks, such as cracks with a width of more than 2 mm; it has a high cost-effectiveness and good crack repair quality and effect.
[0070] The basic principle of the construction method for grouting joints and cracks of cement concrete pavement described in the present invention is: using aggregate, adhesive and waterproof material for combined grouting, which is equivalent to implanting a semi-rigid grouting structure in the joint, and the aggregate is the skeleton of the grouting structure, which serves as the main load-bearing part; the adhesive not only effectively bonds the aggregate, but also makes the grouting structure effectively bonded with the two side walls of the joint, and bears the role of force transmission and dispersion, and its bonding and filling effect with the aggregate enables it to also carry the waterproof material; the waterproof material not only further fills the gaps of the grouting structure and further bonds the aggregate, but also blocks the gaps on the surface of the grouting structure, forming a waterproof thin layer on the surface of the grouting structure, thereby achieving the purpose of three-dimensional waterproofing; the new grouting structure obtained according to the method has multiple technical effects such as load-bearing, bonding, compressible deformation (plasticity), waterproofing, fatigue resistance, and anti-embedding, which can improve the bearing capacity of the joint, driving comfort, and the aesthetics of the road surface, effectively improve the road surface diseases such as the flooding of the base material, the edge gnawing and damage, and extend the service life of the cement concrete road surface.
Claims
1. A method for grouting joints in cement concrete pavement. Features: The steps include: S1. Seam cleaning: Use a seam cleaning machine to cut a new seam with a width of 4 to 6 mm and a depth of 1 / 3 to 2 / 5 of the thickness of the road panel at the joint of the road panel, or use a seam cleaning machine to cut the old filler along the old seam, then clean the seam, grind the inner wall of the seam to make it smooth, and remove the old filler and debris in the seam; S2. Filling in aggregate: After cleaning the joints, fill the joints with clean and dry aggregates, and level the surface of the aggregates until it is flush with the road slab; S3. Pouring adhesive: Evenly pour the adhesive into the aggregate at the joints, and then cure until the adhesive solidifies to form a porous skeleton structure; S4. Pouring waterproof material: After the adhesive solidifies, evenly pour the waterproof material on the joint surface. The waterproof material penetrates into the joint and forms a waterproof layer on the joint surface. The waterproof layer is maintained until the surface is non-sticky, thus forming a grouted structure.
2. A cement concrete pavement joint grouting construction method as claimed in claim 1, Features: In S2, the aggregate includes quartz particles or slag particles, and the particle size is 1 / 5 to 1 / 2 of the joint width.
3. A cement concrete pavement joint grouting construction method as claimed in claim 1, Features: In S3, the adhesive includes components A1 and B1, and the mass ratio of the two components is 2:1 to 5:
1. Component A1 includes 40% to 55% by mass of E51 epoxy resin, 5% to 10% by mass of flexibility modifier, and 30% to 40% by mass of diluent. Component B1 includes 50% by mass of epoxy curing agent and 50% by mass of diluent.
4. A cement concrete pavement joint grouting construction method as claimed in claim 3, Features: In S3, the casting mass ratio of the adhesive to the aggregate is 1:10 to 1:
15.
5. A cement concrete pavement joint grouting construction method as claimed in claim 3, Features: In S3, the physical and mechanical properties of the adhesive are as follows: construction viscosity ≤600mPa·s, tensile strength after curing ≥20MPa, compressive strength after curing ≥35MPa, flexural strength after curing ≥20MPa, 7d tensile bonding strength ≥2.5MPa or substrate damage, solid content ≥50%, surface drying time at room temperature ≤12h, and actual drying time at room temperature ≤24h.
6. A cement concrete pavement joint grouting construction method as claimed in claim 1, Features: In S3, the porosity of the porous skeleton structure is 30% to 40%.
7. A cement concrete pavement joint grouting construction method as claimed in claim 6, Features: In S4, the waterproof material includes components A2 and B2, and the mass ratio of the two components is 3:
7. The A2 component includes 80% to 85% by mass of polyether polyol, 2% to 3% by mass of low molecular weight cross-linking agent, 1% to 2% by mass of water, 10% to 15% by mass of additives, 0.3% to 0.5% by mass of defoaming agent and 0.03% to 0.07% by mass of catalyst; the B2 component is a polyurethane prepolymer; the solid content of the waterproof material is ≥80%; the additives include color paste and filler.
8. A cement concrete pavement joint grouting construction method as claimed in claim 7, Features: In S4, the physical and mechanical properties of the waterproof material are as follows: leveling is smooth and flat, surface drying time ≤16h, elastic recovery rate ≥80%, tensile modulus at 23°C ≤0.4MPa, tensile modulus at -20°C ≤0.6MPa, and adhesion to concrete is not damaged by immersion in water, oil, and artificial aging.
9. A cement concrete pavement joint grouting construction method as claimed in any one of claims 1 to 8, Features: In S4, the horizontal plastic deformation range of the grouting structure is 10% to 15%, and the compressive strength is ≥5MPa.
10. A method for filling cracks in cement concrete pavement. Features: The difference between the cement concrete pavement joint grouting construction method as described in any one of claim 10 is that: in S1, when grouting pavement cracks with a width ≥ 2 mm, there is no need to use a crack cleaning machine to cut the cracks, and the crack cleaning process can be directly performed to grind the inner wall of the crack and remove debris from the crack.
